Sociodemographic and Clinical-pathological Study of Molecular Subtitles of Breast Carcinoma in a Reference Unit of Maranhão - Ana Paula Almeida Miranda Reis; Cecilma Miranda de Sousa Teixeira; Adriano Rêgo Lima de Medeiros; Karlla Zolinda Cantão Chaves; Camila Rosa de Albuquerque; Mateus Rufino Melo (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2021)
Abstract Objective To evaluate the distribution of the main sociodemographic and clinicalpathological characteristics in women with breast cancer according to the molecular profile by immunohistochemistry. Methods A cross-sectional, retrospective, analytical and quantitative study was performed, with an analysis of 137 medical records from January 2015 to December 2018 of women attending the High Complexity in Oncology Unit of the city of Imperatriz, state of Maranhão, Brazil. The immunohistochemical profile of tumors based on the estrogen and progesterone receptor, Human Epidermal growth factor Receptor-type 2 (HER2) overexpression and Ki67 cell proliferation indexwas defined, fromwhich six molecular subtypes were determined: luminal A, luminal B-HER2 negative, luminal B-HER2 positive, triple negative, overexpression of HER2 and inconclusive. Results A total of 52.6% of the patients were postmenopausal, mean age 52.1 years old, brown (56.2%), had a schooling level < 9 years (40%), staging > IIB (52.6%) and 23.4% hadmetastasis. Invasive ductal carcinoma accounted for 84.7%, tumor size was 2 to 5 cm (48.9%), with lymph node involvement (56.2%), axillary lymphadenectomy in 67.2%, andmastectomy in 73.7% of the patients. Themost frequentmolecular subtype was the luminal B-HER2 negative (36.5%), and the luminal A subtype showed characteristics of better prognosis when compared with the others. Conclusion It was concluded that in the association of molecular subtypes with sociodemographic and clinical-pathological characteristics, there were no statistically significant results obtained, except for complementary therapy, referring to hormone therapy, and there was a high index of metastasis at diagnosis, which was a worrying factor and indicative of failures in the screening and early diagnosis of this population.